Variability in the burden of disease estimates with or without age weighting and discounting: a methodological study - Nicholas Buckley; Oluwaseun Egunsola; Jacques Raubenheimer (BMJ Open)
Objectives This study examines the impact of the type of method used on the estimation of the burden of diseases.Design Comparison of methods of estimating disease burden.Setting Four metrics of burden of disease estimation, namely, years of potential life lost (YPLL), non-age weighted years of life lost (YLL) without discounting and YLL with uniform or non-uniform age weighting and discounting were used to calculate the burden of selected diseases in three countries: Australia, USA and South Africa.Participants Mortality data for all individuals from birth were obtained from the WHO database.Outcomes The burden of 10 common diseases with four metrices, and the relative contribution of each disease to the overall national burden when each metric is used.Results There were variations in the burden of disease estimates with the four methods. The standardised YPLL estimates were higher than other methods of calculation for diseases common among young adults and lower for diseases common among the elderly. In the three countries, discounting decreased the contributions of diseases common among younger adults to the total burden of disease, while the contributions of diseases of the elderly increased. After discounting with age weighting, there were no distinct patterns for diseases of the elderly and young adults in the three countries.Conclusions Given the variability in the estimates of the burden of disease with different approaches, there should be transparency regarding the type of metric used and a generally acceptable method that incorporates all the relevant social values should be developed.